Transient neonatal diabetes in a very small sick newborn: A case Report (The Journal of Ad-din Women's Medical College, 2024)
Hyperglycemia in neonatal period is a common metabolic disorder, especially seen in preterm low birth weight and critically ill newborns. The estimated incidence of this condition is around 45%–80%. But Neonatal diabetes mellitus (NDM)is a rare neonatal disease, which has an incidence of approximately 1 in 90,000–160,000 neonates worldwide. Herein we report an extreme preterm, extreme low birth weight, male neonate with transient neonatal diabetes mellitus who was treated with intravenous insulin initially and then subcutaneous insulin Glargine. An adequate glycemia was achieved at 3 weeks of life.The Journal of Ad-din Women's Medical College; Vol. 12 (1), Jan 2024; p 44-46